2006
DOI: 10.1080/00140130600679142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of speech and speech intelligibility on task performance

Abstract: The aim of this study was to find out what are the effects of three different sound environments on performance of cognitive tasks of varying complexity. These three sound environments were 'speech', 'masked speech' and 'continuous noise'. They corresponded to poor, acceptable and perfect acoustical privacy in an open-plan office, respectively. The speech transmission indices were 0.00, 0.30 and 0.80, respectively. Sounds environments were presented at 48 dBA. The laboratory experiment on 36 subjects lasted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 36 publications
6
102
1
4
Order By: Relevance
“…A number of studies have demonstrated that lower STI (or higher privacy) values for task-irrelevant background speech is associated with greater performance (e.g., Ellermeier and Hellbr€ uck, 1998;Haapakangas et al, 2011;Schlittmeier and Hellbr€ uck, 2009). This holds true in visualverbal serial recall (Ellermeier and Hellbr€ uck, 1998;Ebissou et al, 2013;Schlittmeier and Hellbr€ uck, 2009;Haapakangas et al, 2011) as well as in tasks that require processing of meaning and lexical-based retrieval (Haka et al, 2009;Jahncke et al, 2013;Keus van de Poll et al, 2014;Loewen and Suedfeld, 1992;Venetjoki et al, 2006). Yet, as mentioned above, the reason why background speech is less detrimental when its intelligibility is reduced differs, depending on the task at hand.…”
Section: A Why Sound Disrupts Cognitive Performancementioning
confidence: 81%
“…A number of studies have demonstrated that lower STI (or higher privacy) values for task-irrelevant background speech is associated with greater performance (e.g., Ellermeier and Hellbr€ uck, 1998;Haapakangas et al, 2011;Schlittmeier and Hellbr€ uck, 2009). This holds true in visualverbal serial recall (Ellermeier and Hellbr€ uck, 1998;Ebissou et al, 2013;Schlittmeier and Hellbr€ uck, 2009;Haapakangas et al, 2011) as well as in tasks that require processing of meaning and lexical-based retrieval (Haka et al, 2009;Jahncke et al, 2013;Keus van de Poll et al, 2014;Loewen and Suedfeld, 1992;Venetjoki et al, 2006). Yet, as mentioned above, the reason why background speech is less detrimental when its intelligibility is reduced differs, depending on the task at hand.…”
Section: A Why Sound Disrupts Cognitive Performancementioning
confidence: 81%
“…The effects of noise have also been studied in office settings, with which ED clinicians' coordination centers have some similarities. The findings of these studies include that noise is perceived as more annoying and harmful when it is experienced as uncontrollable, unnecessary or unpredictable [3], that ringing phones and intelligible speech are more distracting than most other noises [27], that intelligible speech at 48 dB(A) deteriorates proofreading more than unintelligible noise at 48 dB(A) [28], that exposure to noise at 50 dB deteriorates the performance of cognitively complex tasks more than a nonoise condition [29], and that an equivalent continuous sound level of 51 compared to 39 dB(A) decreases memory for words [30].…”
Section: Related Workmentioning
confidence: 99%
“…Longer distance can reduce auditory distraction by smoothing the perceived variation of sound characters [23,24,25] and by decreasing the signal-to-noise ratio [26,27]. Auditory attention is influenced by other factors such as reverberation [28], the familiarity with the languages of the interfering speech [27,29,30] and combined stimuli. Moreover, substantial intersubject variation exists [31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%